A Class of New Permutation Polynomials over F2n. (15th November 2021) - Liu, Qian; Liu, Ximeng; Zou, Jian
Abstract : In this paper, according to the known results of some normalized permutation polynomials with degree 5 over F 2 n, we determine sufficient and necessary conditions on the coefficients b 1, b 2 ∈ F 2 n 2 such that f x = x 3 x ¯ 2 + b 1 x 2 x ¯ + b 2 x permutes F 2 n . Meanwhile, we obtain a class of complete permutation binomials over F 2 n .